Entrepreneurial Spirit in the Millennial Era for Karang Taruna "Taruna Bakti" Dukuh Karangasem, Sidomulyo Village, Delanggu District, Klaten Regency - Suprayitno; Sutarno Sutarno (Advances In Social Humanities Research, 2024)
This outreach initiative targeted the Karang Taruna Taruna Bakti Dukuh Karangasem community in Sidomulyo Village, Delanggu District, Klaten Regency. The objectives of this initiative encompass enhancing participants' comprehension of entrepreneurship concepts to ensure they possess accurate knowledge. Moreover, it aims to enrich participants' understanding of commencing a business and selecting appropriate business types. Additionally, it seeks to broaden participants' awareness regarding potential business setbacks and strategies for addressing them. The progression of this activity entails several stages: firstly, the selection of participants from the community service, comprising the board and members of Karang Taruna Taruna Bakti Dukuh Karangasem, Sidomulyo Village, Delanggu District, Klaten Regency. Subsequently, the delivery of lecture materials aims to instil an entrepreneurial mindset. Lastly, the evaluation process involves conducting a question-and-answer session before the counselling session to assess participants' initial knowledge of entrepreneurship and business startup techniques. Following the counselling session, the same questions are posed again to evaluate any knowledge enhancement. By comparing the responses before and after the counselling, any improvements in knowledge and comprehension can be determined.